Pride and Prejudice - Austen, Jane (Saga Egmont, 2017)
Pride and Prejudice is a classic novel written by Jane Austen. Set in Georgian England, it follows the lives of the five Bennet sisters as they navigate the pressures and expectations of society in search of love and marriage. With its sharp wit, memorable characters, and timeless commentary on human nature, Pride and Prejudice is a novel that continues to captivate readers of all ages. It is considered a cornerstone of English literature and a classic of romantic fiction.